The Role of Globalisation on Energy Consumption in Nigeria. Implication for Long Run Economic Growth. ARDL and VECM Analysis (Global Journal of Human-Social Science, 2018)
This study explores the relationship between globalization, energy consumption and economic growth for Nigeria by explaining the contributions of financial development and urbanization from 1975 to 2011.The cointegration test proposed by Pesaran and Shin, (1995) and Pesaran et el 2001 is applied to estimate the long-run and short-run relationships among the variables in company of VECM Granger causality framework to establish the direction of causality over the period. After confirming the existence of cointegration, using Johansen approach, the overall results from the estimation of an ARDL energy demand function reveal that in the long run, the index of globalization (measured in three dimensionseconomic, social and overall globalization) leads to a decline in energy consumption especially when combined with the marginal contribution from. of economic growth, financial development and urbanization. This study found financial sector development insignificant in influencing energy consumption in Nigeria. In general, the results highlight the weakness of the Nigerian financial sector in stimulating long run economic growth through resource mobilisation and allocation. Urbanization are the key factors leading to increased energy demand in the long run. We found a feedback relationship between globalization and energy consumption in the long run. The unidirectional causality running from energy consumption to financial development, economic growth.
Keywords: globalisation; financial sector development; energy consumption; ARDL; VECM